Pencegahan Kanker Serviks Melalui Peningkatan Pengetahuan WUS Tentang Tes Inspeksi Visual Asam Asetat - Erna Kasim; Sanghati Sanghati; Ekayanti Hafidah Ahmad; Nurlaela Bilale; Zulfikar Moha (BADAN PENERBIT STIEPARI PRESS, 2023)
Cervical cancer is a disorder that often occurs in women. This disease is dangerous because it can affect the cells in the cervix if not treated immediately. Currently, cervical cancer ranks second among cancers that attack women in the world. According to WHO, 490,000 women in the world every year are diagnosed with cervical cancer and 80% are in developing countries, including Indonesia. In Indonesia, it is estimated that every day 40-45 new cases appear, 20-25 people die, meaning that every 1 hour it is estimated that 1 woman dies due to cervical cancer. This means that Indonesia will lose 600-750 women who are still productive every month. Health promotion and early detection are priorities to prevent and treat disease. The aim of the activity is to prevent cervical cancer through increasing WUS knowledge regarding the Acetic Acid Visual Inspection Test using counseling methods as well as pre-tests before and post-tests after counseling. This can be done to prevent the increase in cervical cancer, namely by providing increased knowledge to women of childbearing age through education about VIA tests. The results show that counseling is significant in increasing WUS' knowledge about the IVA test.